The black widow - Staub, Wendy Corsi; Copyright Paperback Collection (Library of Congress) (New York, New York Harper, an imprint of HarperCollinsPublishers, 2015)
"In the moonlight, a shovelfuls of earth fall on a wooden crate at the bottom of a deep pit. Soon the hole will be filled and covered over with leaves, erasing all trace of the victim below, waking to the horror of being buried alive... Newly divorced Gaby Duran isn't really expecting to find her soul mate on a dating site like InTune. She just needs a distraction from pining over her ex-husband, Ben, and the happy marriage they once had. And she's wise enough to know that online the truth doesn't always match the profile. Almost everyone lies a little--or a lot. But Gaby quickly discovers there is more at stake than her lonely heart. Local singles are going missing after making online connections. And a predator is searching again for the perfect match. One who will fulfill every twisted desire...or die trying,"--page [4] of cover
Includes an excerpt from "Mundy's Landing."
1
Keywords: Divorce -- Fiction; Fear -- Fiction; Man-woman relationships -- Fiction; Murder -- Fiction; Online dating -- Fiction; Secrets -- Fiction; Single people -- Fiction; Truthfulness and falsehood -- Fiction; Suspense fiction